Pregnancy in Tetralogy of Fallot data from the ESC EORP ROPAC registry - Lucia Baris; Magalie Ladouceur; Mark R. Johnson; Mirta Kozelj; Pierluigi Festa; Maryanne Caruana; Kok Han Chee; Thomas Gilljam; Edison Muñoz Ortiz; Johannes J. Duvekot; Roger Hall; Jolien W. Roos-Hesselink (International Journal of Cardiology Congenital Heart Disease, 2021)
Background: Tetralogy of Fallot (TOF) is the commonest cyanotic congenital heart defect. When surgically repaired at young age over 90% of patients reach adult age and most women have a desire to become pregnant However, pregnancy is associated with up to 50% increase in cardiac output and also associated with an elevated risk of arrhythmias and thrombosis. The aim of this study was to describe the outcomes in women with TOF for both mother and baby and to assess the influence of pregnancy on right ventricular (RV) dimensions. Methods: Within the prospective, international ESC EORP Registry Of Pregnancy And Cardiac disease (ROPAC), we describe the outcomes in 421 women with repaired TOF. Primary outcome was the occurrence of maternal cardiovascular events. Secondary outcomes were obstetric and fetal events and RV dilatation and pulmonary valve deterioration. Results: The mean age was 28.8 years and 52.3% were nulliparous. There were no maternal deaths, and heart failure and ventricular tachyarrhythmias complicated respectively 5% and 2% of pregnancies. Almost half of women underwent a Caesarean section (48%). Fetal mortality was 1%, while no neonatal mortality occurred. Pregnancy induced hypertension and HELLP/(pre)eclampsia were found in 3% and 1% respectively. Preterm delivery was observed in 14% and 10% had low birth weight. RV dilatation occurred in 49% and was significantly associated with moderate and severe pulmonary regurgitation (PR). Conclusion: Women with repaired TOF tolerate pregnancy relatively well, with no maternal mortality, and low complication rate. Pulmonary regurgitation predicts RV dilatation. Fetal and neonatal outcomes were also favorable and women should be counselled as low to moderate risk. However, nearly half of women underwent Caesarean section, while probably more women should have a vaginal delivery.